Effectiveness of ethanol extract of kirinyuh leaf (Chromolaena odorata L) on the increase the fibroblasts and angiogenesis in nose mucosa of rabbit (lepus curpaneums) - Teuku Husni TR; Novina RAHMAWATI; Irnawati IRNAWATİ (Journal of Syiah Kuala Dentistry Society, 2022)
Wounds are the loss or damage to a part of the body's tissue that disrupts the tissue's continuity.Kirinyuh plants have been used as a traditional wound treatment in various cultures worldwide. Purpose: To provethe effectiveness of topical ethanol extract of kirinyuh leaf ointment on increasing angiogenesis and fibroblasts inhealing rabbit nasal mucosal incisions. Methods: This research is an experimental study with a posttest-only controlgroup design. The research subjects consisted of 25 rabbits divided into five groups; one positive control group, onenegative control group, and three treatment groups. The positive control group was given betadine ointment, thenegative control group was made by incision of the nasal mucosa, and the three treatment groups were given 5%,10%, and 15% concentrations of kirinyuh leaf ethanol extract ointment. Results: The results showed thatadministering kirinyuh leaf ethanol extract ointment with concentrations of 5%, 10%, and 15% could improve thehealing of rabbit nasal mucosal incisions (Lepus Curpaneums), which were characterized by an increase in thenumber of fibroblasts and angiogenesis. In general, the increase in fibroblast cells between the concentrations of theethanol extract of kirinyuh leaf ointment was significantly different (p0.05) with a negative correlation (r= -0.538).Meanwhile, there was no significant difference in the amount of angiogenesis between concentrations (p0.05) witha positive relationship (r=0.099).Conclusion: the ethanol extract of kirinyuh leaf ointment applied topically improvesthe healing of rabbit nasal mucosal incisions KEYWORDS: ethanol extract of kirinyuh leaf ointment, wound healing, fibroblast, angiogenesis